KETERKAITAN AGEN BERAS DENGAN STAKEHOLDER RANTAI PASOK DI KECAMATAN BATURAJA TIMUR - Safitri, Arumdyah Ramadhani; Pusvita, Ema; Ogari, Putri Ayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study has directions to find out the relation to find out the relationship between rice agents and supply chain stakeholders in East Baturaja District. This research method was carried out using a quantitative method in which the research used Spearman’s rank analysis.Information material was obtained by distributing questionnaires and information material obtained from rice agent business actors in East Baturaja District. The results of this study are the results of the relationship between rice agents and supply chain stakeholder in East Baturaja District, which consist of: capital, rice millers, retailers,labor, consumers and transportation. Of the six factors, three factors have a very close relationship with stakeholders to rice agents in East Baturaja District, namely capital rice agents, consumers and retailers, and three factors that have a very weak relationship with rice agent stakeholders in East Baturaja District.